Daily, limited access to methamphetamine self‐administration during pregnancy leads to increased methamphetamine sensitivity in adult offspring. Issue 1 (9th December 2022) - Pareek, Tanya; Platt, Donna M.; Rüedi‐Bettschen, Daniela
Abstract: Methamphetamine use by women, even throughout pregnancy, is common. But there is limited knowledge about the effects in prenatally methamphetamine‐exposed children. This study investigated how prenatal methamphetamine exposure in rats, via maternal i.v. self‐administration, affected the sensitivity of adult offspring to methamphetamine in comparison with controls. The offspring were generated from dams either self‐administering methamphetamine daily under limited‐access conditions prior to and throughout pregnancy, or their respective saline‐yoked control dams. Spontaneous and methamphetamine‐induced locomotor activity was assessed in male and female offspring of both exposure groups after a range of methamphetamine doses. In a separate group of offspring, acquisition of i.v. methamphetamine self‐administration, responding under fixed and progressive ratio schedules of methamphetamine reinforcement, and reinstatement of extinguished drug‐seeking behavior were assessed. Methamphetamine dose‐dependently increased locomotor activity in both exposure groups. However, methamphetamine‐exposed males showed significantly enhanced locomotor activity compared with controls at 1 mg/kg, and methamphetamine‐exposed females showed significantly enhanced locomotor activity compared with controls at 3.2 mg/kg. Methamphetamine‐exposed offspring of both sexes acquired methamphetamine self‐administration faster and showed overall higher levels of methamphetamine‐induced reinstatement compared with controls. Taken together, these results indicate that prenatal methamphetamine exposure to relatively low levels alters methamphetamine sensitivity in male and female adult offspring.